Incidencia de la violencia familiar en el rendimiento académico de los estudiantes de la institución educativa "virgilio purizaga aznarán", provincia de pacasmayo, departamento la libertad. - Celis Grados, Diana Roxana (2013)
The aim of the research work is to determine the effects of domestic violence on school performance of students in the Institution Educative “Virgilio Purizaga Aznaran” located in distrite of Pacasmayo of the Department of the La Libertad. The sample consisted of 81 students from 5 °and 6° AB The data obtained through the application of a survey, which established their perception of violence in their homes, were statistically analyzed using the Excel program. The result was a high percentage of students are affected by domestic violence and therefore have poor academic performance are victims of violent situations 56% of students surveyed the percentage of students claiming to be abused physically and psychologically by 66 un34%. The student community of the town that is affected by a high number of situation sof domestic violence. There are many variables that can be taken into account to improve educational performance and link the achievements of the school, family and social context of the student seeking to improve their quality of life. To achieve this, teachers need to have clear understanding of the school context, family and social student, and the factors that positively and negatively influence their development processes of these factors is domestic violence, which in addition to have great impact on student academic performance has negative influence on their personal and social development and affects the quality of life of many students of the Institute Educative “Virgilio Purizaga Aznaran”: Violence, Family, performance, domestic abuse, physical, psychological. Therefore has as objective to give to know how the domestic violence is affecting young people in the I. E "Virgilio Purizaga Aznaran”.